HUSBAND INVOLVEMENT IN DISCONTINUING IMPLANT CONTRACEPTIVE USE AMONG MARRIED WOMEN IN INDONESIA - Diya Susanti; Ni’mal Baroya; Andrei Ramani (The Indonesian Journal of Public Health, 2022)
Introduction: Efforts to control population growth in Indonesia by increasing the use of contraceptives continue to be improved so that the TFR of 2.1 in 2024 can be achieved. However, in practice, there is still discontinuation of the use of contraceptive methods. One of them is the implant method. This research aims to analyze husband involvement of implant discontinuation in Indonesia. Method: This study used a cross-sectional study design. Data of this study were based on the results of IDHS 2017, with 1153 samples. This research was analyzed using Chi-square test Logistic Regression test with significance level α=0.05. Result: Characteristics of respondents, husband's employment, decision to use, consent to use, preferences of husbands for the number of children, determination of income for FP device and categories of husband involvement are not related significantly while the husband's education level and discussions about FP were significant with implant discontinuation. Variables that become risk factors for implant discontinuation are respondents who do not work, wealth index (very poor, poor, middle and rich), education level of respondents who do not attend school and academy level; husband not involved in the decision to use the FP device, does not give consent to the use the FP device;  preference of husbands for the number of children is the same/more than the respondent; and husband not involved in determining the income for the FP device. Conclusion: To reduce the drop-out rate for implants, it is necessary to increase the husband's education and involvement in discussing family planning.